Detailed analysis on the reflection component for the black hole candidate MAXI J1348-630. Issue 3 (4th February 2022) - Jia, Nan; Zhao, Xueshan; Gou, Lijun; García, Javier A; Liao, Zhenxuan; Feng, Ye; Li, Yufeng; Wang, Yuan; Li, Huixian; Wu, Jianfeng
ABSTRACT: The black hole candidate MAXI J1348-630 was discovered in 2019 January 26, with the Gas Slit Camera (GSC) on-board MAXI . We report a detailed spectral analysis of this source by using the archived data of NuSTAR . A total of nine observations covered the complete outburst evolution of MAXI J1348-630 from the hard state to the soft state and finally back to the hard state. Additionally, the intermediate state is found in the transition from the hard state to the soft state. We use the state-of-the-art reflection model relxill family to fit all the nine spectra, and the spectra from two focal plane module detectors of NuSTAR are jointly fitted for each observation. In particular, we concentrate on the results of the black hole spin parameter and the inclination of the accretion disc. Based on the analysis of the inner radius of the accretion disc, we obtain the spin parameter a_* =0.78_-0.04^+0.04, and the inclination angle of the inner disc i = 29.2_-0.5^+0.3 °. Furthermore, we also find that when the black hole is in the hard state, the accretion disc would show a significant truncation. The high iron abundance and ionization of the accretion disc obtained in the fitting results can be possibly explained by the high density of the accretion disc.